Mild dehydration does not influence performance or skeletal muscle metabolism during simulated ice hockey exercise In men - Palmer, M. S.; Heigenhauser, G. J. F.; Duong, M. L.; Spriet, L. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
This study determined whether mild dehydration influenced skeletal muscle glycogen use, core temperature or performance during high-intensity, intermittent cycle-based exercise in ice hockey players vs. staying hydrated with water. Eight males (21.6 ± 0.4 yr, 183.5 ± 1.6 cm, 83.9 ± 3.7 kg, 50.2 ± 1.9 ml·kg-1·min-1) performed two trials separated by 7 days. The protocol consisted of 3 periods (P) containing 10 × 45-s cycling bouts at ~133% VO2max, followed by 135 s of passive rest. Subjects drank no fluid and dehydrated during the protocol (NF), or maintained body mass by drinking WATER. Muscle biopsies were taken at rest, immediately before and after P3. Subjects were mildly dehydrated (-1.8% BM) at the end of P3 in the NF trial. There were no differences between the NF and WATER trials for glycogen use (P1+P2; 350.1 ± 31.9 vs. 413.2 ± 33.2, P3; 103.5 ± 16.2 vs. 131.5 ± 18.9 mmol·kg dm-1), core temperature (P1; 37.8 ± 0.1 vs. 37.7 ± 0.1, P2; 38.2 ± 0.1 vs. 38.1 ± 0.1, P3; 38.3 ± 0.1 vs. 38.2 ± 0.1 °C) or performance (P1; 156.3 ± 7.8 vs. 154.4 ± 8.2, P2; 150.5 ± 7.8 vs. 152.4 ± 8.3, P3; 144.1 ± 8.7 vs. 148.4 ± 8.7 kJ). This study demonstrated that typical dehydration experienced by ice hockey players (~1.8% BM loss), did not affect glycogen use, core temperature, or voluntary performance vs. staying hydrated by ingesting water during a cycle-based simulation of ice hockey exercise in a laboratory environment.